Barreiras para nutrição adequada em UTI pediátrica - Cabral, Daiane Drescher (2014)
Objective: Assess the offer and the energy restriction of patients hospitalized in a PICU. Methods: This is a prospective observational cohort descriptive, conducted from 01/09/2009 to 31/08/2010 in patients admitted to the PICU of a university hospital. Some additional data were collected from medical records of patients in Service Medical Records. The study was approved by the Ethics in Research Committee. The energy offer was received compared to Basal Energy Expenditure (BEE) and restrictions were also evaluated in the energy offer of patients, by analyzing the period No Initial Offer Energy and Pauses in Energy Offer, as well as the reason for the same. Data were collected during admission and hospitalization. Outcomes such as mortality, malnutrition, severity, organ dysfunction, length of hospitalization, mechanical ventilation, vasoactive drugs and adequacy of energy offer were evaluated. Results: The sample consisted of 475 admissions. Interned No Initial Offer Energy 97.5% patients. 55.2% of these initiated within the first 24 hours. The surgery (35%), critical clinical condition (30%) and examination (21%) on admission were not primarily responsible for introducing the initial energy offer. The PIM2> 6, acute illness, infection, hematologic, gastrointestinal, and renal dysfunction, MODS on admission, mechanical ventilation, vasoactive drugs and patients who had prolonged hospitalization are associated with an increased time to onset of nutrition (p <0.05 ). There were a total of 379 Pauses in Energy Offer during hospitalization in 175 patients. Of these, 91% reached the BEE to discharge, taking 24-502 hours. The gastrointestinal dysfunction (89%), intubation/extubation (71%) and fluid restriction (31%) during hospitalization, were primarily responsible for Pauses in the Energy Offer. The patients under one year, malnourished, PIM2> 6, clinical patients with infection with respiratory and liver dysfunction with MODS, who used mechanical ventilation, vasoactive drugs and those who had prolonged hospitalization are associated with a greater number of pauses (p <0.05). Prolonged hospitalization and mechanical ventilation are independently associated with delay to the beginning of the energy offer (greater than 38 hours) and the presence of pauses in the diet. BEE reached 79% of patients, 4% achieved only after the 5th day, being 75% of the total considered adequate energy offer and 25% in inadequate energy offer. PIM2 patients with>6, respiratory, hepatic and hematologic dysfunction, with MODS, who used vasoactive drugs and who died reached less adequate energy offer during hospitalization (p <0.05). Conclusions: The Majority of patients hospitalized No Initial Offer Energy . Of these, only 55.2% started their nutrition in the first 24 hours. The surgery, critical clinical condition and the need to perform tests on admission were not primarily responsible for introducing the initial energy supply for patients. The gastrointestinal dysfunction, intubation/extubation and fluid restriction during hospitalization, were primarily responsible for pauses in the energy offer. Prolonged hospitalization and the use of mechanical ventilation are independently associated with delay to the start of the energy offer and with the presence of food pauses.